PP.27.19: CARDIAC INVOLVEMENT IN SYSTEMIC AUTOIMMUNE DISEASES. (June 2015) - Toujani, S.; Daoud, F.; Aydi, Z.; Baili, L.; Dhaou, B. Ben; Boussema, E.; Boussema, F.
Abstract : Objective: The heart is frequently affected in systemic autoimmune diseases. Any part of the heart can be affected, including the pericardium, myocardium, valves, and the conduction system. The aim of our study is to outline the cardiac manifestations of the systemic autoimmune diseases. Design and method: This retrospective study concerned cases of cardiac involvement due to systemic autoimmune diseases; followed by internal diseases department between 2000 and 2015. Results: They were 26 cases with 6 men and 20 women. The mean age at onset of cardiac involvement was 32 years. The most common symptoms were progressive dyspnea and chest pain occurring in respectively 50% and 20% of cases. Asymptomatic heart involvement occurred in 30% of cases. Pericarditis was the main heart manifestation occurring in 77% of cases. Myocarditis was observed in all the other cases. The causes of pericarditis included: Systemic Lupus Erythematosus (65%), Systemic Sclerosis (8%), lupus scleroderma overlap, mixed connective tissue disease and adult still's disease in respectively one case. Vasculitis complicated with pericarditis was seen in two cases: takayashu vasculitis and Churg Strauss syndrome. The etiologies of myocarditis were: Systemic Lupus Erythematosus (3 cases), Churg Strauss syndrome (1 case) and Kawasaki disease in a sixteen years old patient. The treatment was based on corticoids in all cases. Immunosuppressive treatment with cyclophosphamide was indicated in seven cases. The response to therapy was favorable in 92% of cases. Conclusions: Cardiac involvement in patients with systemic autoimmune diseases is common. Improved technology has made the diagnosis of many of these conditions easier. The prognosis is generally conserved.